Depression in family caregivers of the chronically ill - Clemente, Miguel (2012)
Chronic illness affects the individual who suffers as all those who maintain relationships with patients, and especially to his family and caregivers. Over 50% of caregivers show high levels of depression and anxiety, which vary depending on the duration and intensity of the clinical condition of the person cared for. We used a non-probability sampling technique of incidental type, selecting a total of 300 people who were divided into three subsamples of 100 subjects each; Relatives caring for people who are totally dependent; Relatives caring for children and youth totally dependent and finally family caregivers of people with diseases of mild dependence, evaluated with the Beck Depression Inventory. We created a questionnaire that included questions on personal characteristics, social and labor, both of the dependent person and the family caregiver. We could observe that most families do not have levels of depression or this is of a mild level unlike other studies reviewed.